2021
DOI: 10.1038/s41467-021-26349-x
|View full text |Cite
|
Sign up to set email alerts
|

Harmonizing corporate carbon footprints

Abstract: Global greenhouse gas emissions need to reach net-zero around mid-century to limit global warming to 1.5 °C. This decarbonization challenge has, inter alia, increased the political and societal pressure on companies to disclose their carbon footprints. As a response, numerous companies announced roadmaps to become carbon neutral or even negative. The first step on the journey towards carbon neutrality, however, is to quantify corporate emissions accurately. Current carbon accounting and reporting practices rem… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…Analyzing GHG emissions during the refining process in key refineries will support the targeted implementation of emission reduction technologies, and thus drive countries and enterprises to take action on mitigation. 9 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…Analyzing GHG emissions during the refining process in key refineries will support the targeted implementation of emission reduction technologies, and thus drive countries and enterprises to take action on mitigation. 9 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…For example, an analysis of food and beverage companies demonstrated that 7 of the largest 50 companies did not report emissions, and that reporting, especially of scope 3 emissions, is incomplete [ 35 ]. A case study of the tech industry found that corporate reports omit half of company GHG emissions [ 36 ], while a study of manufacturing companies found low levels of emission disclosure [ 37 ]. In addition, while all but one company in our study had reported climate change targets, few of these targets covered scope 3 emissions, again comparable with other industry targets [ 35 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Data gaps and inconsistent application of accounting standards lead to widespread undercounting of emissions. For example, only one-third of suppliers provide information on their indirect emissions to customers 4 , leading companies to report different levels of emissions for similar activities. In the technology sector, proper inclusion of indirect emissions from purchased goods and product usage can double emissions estimates 4 .…”
Section: Reliability Constraintsmentioning
confidence: 99%